A critical disability theory analysis of wrongful life/birth actions in Israel. (1st January 2013) - Karako-Eyal, Nili
Wrongful life/birth actions raise difficult questions. The Israeli Supreme Court of Justice's recent ruling in the case of Hamer (2012) reflects these difficulties. The court decided that wrongful life actions should not be admitted. By contrast, wrongful birth actions were approved. This paper offers a critical disability theory analysis of the decision in Hamer. The author claims that the court's refusal to acknowledge wrongful life actions constitutes an important positive legal narrative. Nevertheless, the judicial narrative provided in other parts of the decision makes only a marginal contribution to the positive social structuring of disability. Therefore, the author suggests a new approach that is based on the parents' right to autonomy. The author claim that this position does not involve negative connotation towards people with disabilities and enable the court to compensate the parents for the damages they suffered.